Fenomena Petani Milenial Di Dusun Campagaya Kabupaten Gowa - Nurhidayah .; Firdaus W Suhaeb; Mauliadi Ramli (PREDESTINATION: Journal of Society and Culture, 2023)
AbstractThis research was conducted with the aim of knowing (1) What are the factors driving youth to become millennial farmers in Campagaya Hamlet (2) How is the application of agricultural technology by millennial farmers. The results of this study conclude that 1. The driving factors for young people to become millennial farmers are: enthusiasm for work, and being able to determine expenditure and income 2. Application of agricultural technology by millennial farmers. The farmers of the Campagaya Hamlet community can adapt to current demands such as cooperation in farming, the use of modern tools used in working on gardens or rice fields as well as modern tools for harvesting rice in the form of auto sangking (reaper machines), modern tools for planting corn in the form of pa'lamongang biralle (corn seeder). machin) and machine tools for working on land (yanmar blender machine). And the form of role and family support is very important in order to cover economic needs. Youth use cellphones as a medium or source of information on how to use modern technological machines and find out how conditions change in managing land to start farming and how farming communities use traditional to modern tools.Keywords: Phenomena, Farmers, Youth, Technologists